The Labor Theory of Value:: A Critique of Carson’s Studies in Mutualist Political Economy - Murphy, Robert P. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
Kevin Carson’s studies in Mutualist Political Economy (2004) is an impressive work. It first attempts to rehabilitate the classical labor theory of value (by giving it a subjectivist spin), and then traces the history of capitalism to show that it was founded by, and necessarily relies upon, State aggression. Carson finally ends by sketching his vision of a just world based on the principles of “mutualism” in which labor retains its product and every actor internalizes the full costs of his or her decisions. This article argues that his rebuttals to Böhm-Bawerk’s famous critique of the labor theory of value, as well as Carson’s attempted rehabilitation of the theory along subjectivist lines, utterly fail.